Regulation of Early Childhood Socio-Emotional Behavior through Teacher–Parent Collaboration at TKK Bunda Pengantara Rahmat Ngedukelu: Pengendalian Perilaku Sosial Emosional Anak Usia Dini Melalui Kolaborasi Guru dan Orang Tua Di TKK Bunda Pengantara Rahmat Ngedukelu - Maria Sindrela Wea; Efrida Ita; Yasinta Maria Fono; Gde Putu Arya Oka (Bestari: Jurnal Pendidikan dan Kebudayaan, 2026)
Early childhood socio-emotional behavior plays a crucial role in children's overall development. This study aims to describe the process of controlling socio-emotional behavior in early childhood and the forms of collaboration between teachers and parents at TKK Bunda Pengantara Rahmat Ngedukelu. A descriptive qualitative method with a case study approach was employed, and data were collected through observation, interviews, and documentation. The findings reveal that the management of children's socio-emotional behavior is carried out through synergistic collaboration between teachers who apply cognitive functions (emotional literacy) and parents who apply affective functions (emotional reassurance and affection). This collaboration is realized through routine communication during school drop-off and pick-up, the alignment of rules between school and home to prevent value confusion, and periodic meetings as a structured monitoring system. These interventions have proven effective in transforming children's negative behaviors into positive socio-emotional competencies. This study contributes practical strategies for school-family collaboration in early childhood education, while also raising awareness of the vital role of parents as children's primary emotional support figures.